2010
DOI: 10.1089/pho.2009.2500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Use of Laser Phototherapy (λ660 or 790 nm) on the Survival of Cutaneous Flaps on Diabetic Rats

Abstract: LPT was effective in increasing angiogenesis as seen on irradiated subjects and was more pronounced when IR laser light was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…Diabetes mellitus (DM) is characterized by elevated blood glucose levels, an impaired blood supply, and increased production of reactive oxygen species (ROS) [1]. Chronic ROS generation is implicated in the pathogenesis of many illnesses, including atherosclerosis and inflammation [2, 3].…”
Section: 0 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus (DM) is characterized by elevated blood glucose levels, an impaired blood supply, and increased production of reactive oxygen species (ROS) [1]. Chronic ROS generation is implicated in the pathogenesis of many illnesses, including atherosclerosis and inflammation [2, 3].…”
Section: 0 Introductionmentioning
confidence: 99%
“…However, the synthesis of large amounts of NO can produce nitrosative stress by reacting with superoxide to form peroxynitrite. Many authors have proposed that low level-laser therapy (LLLT) is able to influence oxidative stress parameters as well as to change the activity of antioxidant enzymes and the production of ROS [1]. Over the last decade the literature has been reported an increased interest in the application of photobiomodulation using different light sources in diseases related to increased oxidative stress, but the mechanisms involved in this response remain unclear, especially in relation to the effects of LLLT on the mitochondrial respiratory chain and on biomarkers of oxidative stress.…”
Section: 0 Introductionmentioning
confidence: 99%
“…At a fluence between 3.7 and 10 J/cm 2 , splinted irradiated wounds responded better and healed quicker than nonirradiated splintered wounds. Santos et al [76] irradiated cutaneous flaps with poor circulation in diabetic Wistar rats either with 680 or 790 nm (2.5 J/cm 2 per point). It was shown that angiogenesis was increased in irradiated rats compared to control, non-irradiated rats, more so when a wavelength of 790 nm was used.…”
Section: Phototherapymentioning
confidence: 99%
“…The variables used for this analysis are shown in Table 1. 13 These variables were used previously 13,21 and included inflammatory reaction, re-epithelialization, number of fibroblasts, and amount of collagen deposition and neoangiogenesis. The scoring system was based upon the number of samples with the observed grading.…”
Section: Polarized Light On Diabetic Wound Healingmentioning
confidence: 99%